Some Less Known Ethnomedicinal uses from Mysore and coorg districts, Karnataka, Southern India - Kshirsagar, R. D. (Medknow Publications & Media Pvt Ltd, 2001)
Present communication deals with 51 less known uses belonging to 39 medicinal plants which are being used traditionally in Karnataka, and are not well known for its said efficacies for curing respective disorders. Each use has been given under correct botanical name, family, local name, locality in particular district and finally the collection number